(3JNGejS GdbUGFO GdaRGRjIs - (3eLghds; (3CHh RjO YHO GdQMef Hf jNdaJjf GdaRGRjs
(3ChdgG (B:s
(3baG Hi CUjMGHi Ydi GdNaja hGegdG hdG JHZjG Yf bUO WjHHI eYOdG HgG HOQ Je fhQg bO JcedG s
(3BNQgG (B:s
(3CVMi GdHcGA Mdja ef aGQbJg dG YjH ai LRYi Ydjc hdjJg cGf GdHcGA HebdJi jOhe s
(3GdfSNI HgG MhGTs
(3eQJHI Ydi MQha GdeYLes
(3hai ChdgG hbajI CQNJ HSfI (B1239 s
(3hYdi ghGeTgG TQhM cKjQIs
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
Keywords: (3GdCOHs